Will life find a way? Evolution of marine species under global change. (October 2016) - Calosi, Piero; De Wit, Pierre; Thor, Peter; Dupont, Sam
Abstract: Projections of marine biodiversity and implementation of effective actions for its maintenance in the face of current rapid global environmental change are constrained by our limited understanding of species' adaptive responses, including transgenerational plasticity, epigenetics and natural selection. This special issue presents 13 novel studies, which employ experimental and modelling approaches to (i) investigate plastic and evolutionary responses of marine species to major global change drivers; (ii) ask relevant broad eco‐evolutionary questions, implementing multiple species and populations studies; (iii) show the advantages of using advanced experimental designs and tools; (iv) construct novel model organisms for marine evolution; (v) help identifying future challenges for the field; and (vi) highlight the importance of incorporating existing evolutionary theory into management solutions for the marine realm. What emerges is that at least some populations of marine species have the ability to adapt to future global change conditions. However, marine organisms' capacity for adaptation appears finite, due to evolutionary trade‐offs and possible rapid losses in genetic diversity. This further corroborates the idea that acquiring an evolutionary perspective on how marine life will respond to the selective pressure of future global changes will guide us in better identifying which conservation efforts will be most needed and most effective.